Downregulation of PGI2 pathway in Pulmonary Hypertension Group-III patients. (September 2020) - Ozen, Gulsev; Amgoud, Yasmine; Abdelazeem, Heba; Mani, Salma; Benyahia, Chabha; Bouhadoun, Amel; Tran-Dinh, Alexy; Castier, Yves; Guyard, Alice; Longrois, Dan; Silverstein, Adam M.; Norel, Xavier
Highlights: Decreased PGIS expression in pulmonary artery from PH Group-III patients. Decreased 6-keto-PGF1α levels in pulmonary artery and lung tissue from PH Group-III patients 6-keto-PGF1α levels released from hPASMC were inversely correlated with mPAP in PH Group-III patients. Abstract: Pulmonary hypertension (PH) is a progressive and life-threating lung disorder characterized by elevated pulmonary artery pressure and vascular remodeling. PH is classified into five groups, and one of the most common and lethal forms, PH Group-III is defined as PH due to lung diseases and/or hypoxia. Due to the lack of studies in this group, PH-specific drug therapies including prostacyclin (PGI2 ) analogues have not been approved or recommended for use in these patients. PGI2 is synthesized by the PGI2 synthase (PGIS) enzyme, and its production is determined by measuring its stable metabolite, 6-keto-PGF1α . An impaired PGI2 pathway has been observed in PH animal models and in PH Group-I patients; however, there are contradictory results. The aim of this study is to determine whether PH Group-III is associated with altered expression of PGIS and production of PGI2 in humans. To explore this hypothesis, we measured PGIS expression (by western blot) and PGI2 production (by ELISA) in a large variety of preparations from the pulmonary circulation including human pulmonary artery, pulmonary vein, distal lung tissue, pulmonary artery smooth muscle cells (hPASMC), and bronchi in PH Group-III ( n = 35) and control patients ( n = 32). Our results showed decreased PGIS expression and/or 6-keto-PGF1α levels in human pulmonary artery, hPASMC, and distal lung tissue derived from PH Group-III patients. Moreover, the production of 6-keto-PGF1α from hPASMC positively correlated with PGIS expression and was inversely correlated with mean pulmonary artery pressure. On the other hand, PH Group-III pulmonary veins and bronchi did not show altered PGI2 production compared to controls. The deficit in PGIS expression and/or PGI2 production observed in pulmonary artery and distal lung tissue in PH Group-III patients may have important implications in the pathogenesis and treatment of PH Group-III.